2007
DOI: 10.1007/s00442-007-0937-2
|View full text |Cite
|
Sign up to set email alerts
|

Larval amphibian growth and development under varying density: are parasitized individuals poor competitors?

Abstract: Population density and infection with parasites often are important factors affecting the growth and development of individuals. How these factors co-occur and interact in nature should have important consequences for individual fitness and higher-order phenomena, such as population dynamics of hosts and their interactions with other species. However, few studies have examined the joint effects of density and parasitism on host growth and development. We examined the co-influences of rearing density and parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…Tadpoles had higher survival at low density and in the absence of parasitism, consistent with most previous studies of echinostomes in tadpoles (Fried et al 1997, Schotthoefer et al 2003, Belden 2006, Holland et al 2007, Rohr et al 2008a, though not all studies have found tadpole mortality due to infection (Koprivnikar et al 2008, Orlofske et al 2009). Also as predicted, high tadpole density led to delayed development and slower growth rates, and tadpoles responded to competition and predation by increasing and decreasing their activity levels, respectively.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Tadpoles had higher survival at low density and in the absence of parasitism, consistent with most previous studies of echinostomes in tadpoles (Fried et al 1997, Schotthoefer et al 2003, Belden 2006, Holland et al 2007, Rohr et al 2008a, though not all studies have found tadpole mortality due to infection (Koprivnikar et al 2008, Orlofske et al 2009). Also as predicted, high tadpole density led to delayed development and slower growth rates, and tadpoles responded to competition and predation by increasing and decreasing their activity levels, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…However, the echinostome-infected snail had no significant effect on mass at metamorphosis. These two results together imply slower growth rates with parasitism, likely because antiparasite responses were costly or because echinostome infection caused direct sub-lethal effects on growth (Fried et al 1997, Koprivnikar et al 2008. This reduction of growth with echinostome exposure was probably not driven by selective mortality of larger tadpoles, because smaller tadpoles are generally less tolerant of echinostome infection (Schotthoefer et al 2003, Holland et al 2007, or by thinning due to parasite-induced mortality, which should reduce competition and accelerate growth (Peacor and Werner 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cercariae were obtained as previously detailed [31] after local collection of aquatic gastropods that serve as first intermediate hosts (Stagnicola elodes here), and were identified based on the presence of 43 collar spines [32]. Cercariae of Echinoparyphium spp.…”
Section: Methodsmentioning
confidence: 99%
“…However, macroparasites are often highly aggregated in nature, with a few individual hosts harboring high infections while the majority of the host population possesses much lower parasite burdens (Shaw et al, 1998). This aggregation of parasites likely occurs in populations of tadpoles, but the effects of more common, modest levels of infection on growth, development, and competitive ability have only recently been investigated (Koprivnikar et al, 2008) and require additional examination. Furthermore, seasonal timing of infection associated with amphibian life histories should also be addressed (Schotthoefer et al, 2003).…”
mentioning
confidence: 99%